Long-Term Care Partnership Effects on Medicaid and Private Insurance - Joan Costa-i-Font; Nilesh Raut (Center for Economic Studies and ifo Institute (CESifo), 2021)
Can the expansion of Medicaid, a means-tested health and long-term care insurance, be slowed down by incentivising the purchase of private long-term care insurance (LTCI)? We study the implementation of the long-term care insurance partnership (LTCIP) program, a joint federal and state-level program that intended to promote LTCI coverage. Drawing on a difference-in-differences (DD) design we study the effect of the rollout of the LTCIP program between 2005 and 2016 on both LTCI uptake and Medicaid eligibility, and we estimate the effect on Medicaid savings. Drawing on a difference-in-differences (DD) design, we find that, unlike previous estimates, the introduction of the LTCIP does significantly increase LTCI coverage and reduce the uptake of Medicaid. The effects are driven by the introduction of LTCIP in states after 2010. We estimate that the adoption of LTCIP has given rise to an average Medicaid saving of 36 for every 65-year-old. This suggests scope for LTCI arrangements to reduce Medicaid spending.
Keywords: I18; H11; H24; 330; long-term care partnerships; long-term care insurance; Medicaid; United States; difference-in-differences